Brain arteriovenous malformations and seizures: an Italian study. Issue 3 (13th July 2013) - Galletti, F; Costa, C; Cupini, L M; Eusebi, P; Hamam, M; Caputo, N; Siliquini, S; Conti, C; Moschini, E; Lunardi, P; Carletti, S; Calabresi, P
Abstract : Objective: To evaluate seizures as first clinical manifestation of brain arteriovenous malformations (AVMs), in relation to angioarchitectural features of these vascular anomalies. Methods: We performed a prospective observational study, collecting records of patients with AVMs consecutively admitted to the Neurological and Neurosurgery Units of Perugia University and to the Neurosurgery Unit of Terni Hospital, during a 10-year period (1 January 2002 to 1 June 2012). Two groups of patients, with or without seizures as AVM first presentation, were analysed to identify differences in demographic and angiographic features. A multivariate logistic regression model was also developed. Results: We examined 101 patients with AVMs, 55 male and 46 female. Seizures were the initial clinical manifestation in 31 (30.7%) patients. We found a significant difference (p<0.05) between two groups of patients, with or without seizures as AVM first presentation concerning location, side, topography and venous drainage. A multivariate logistic regression model showed that clinical presentation with seizures was correlated with a location in the temporal and frontal lobes, and with a superficial topography. The strongest association (OR 3.48; 95% CI 1.77 to 6.85) was observed between seizures and AVM location in the temporal lobe. Conclusions: Vascular remodelling and haemodynamic changes of AVMs might create conditions for epileptogenesis. However, here we show that malformations with specific angiographic characteristics are more likely to be associated with seizures as first clinical presentation. Location is the most important feature related to epilepsy and in particular the temporal lobe might play a crucial role in the occurrence of seizure.